Phylogenetic Analysis of Sulawesi Endemic Butterfly Papilio blumei Using the COI (Cytochrome Oxidase I) Gene - Rizkia Khairunnisa; I Made Budiarsa; Isnainar Isnainar; Manap Trianto; Yulia Windarsih; Fatmah Dhafir (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Phylogenetics is a method used to study and analyze evolutionary relationships among living organisms. In phylogenetic studies, organisms that share similar traits or characteristics are considered to have close evolutionary relationships, as they are assumed to have originated from a common ancestor. Papilio blumei is characterized by wings with a bright, iridescent green coloration. This study aimed to describe the phylogenetic relationship of P. blumei based on the cytochrome oxidase subunit I (COI) gene. Sampling was conducted using a roaming (exploratory) method. DNA was isolated using the GS 100gSYNCTM DNA Extraction Kit. DNA amplification was performed using COI primers (LCO1490 forward and HCO2198 reverse) through polymerase chain reaction (PCR). DNA electrophoresis was carried out using 1% agarose gel, a UV transilluminator, and a gel documentation system. Data were analyzed using GeneStudio, DnaSP, BLAST, DNASTAR, and MESQUITE software, and phylogenetic reconstruction was performed using the Neighbor-Joining and Maximum Likelihood methods in MEGA 11 with the Kimura 2-parameter model and 10,000 bootstrap replications. The results showed that the DNA samples had a 99.50% identity with the reference sequences in GenBank. Genetic variation analysis revealed two haplotypes with haplotype diversity (hd = 0.600 ± 0.175) and nucleotide diversity (phi = 0.00051 ± 0.00015). Phylogenetic tree reconstruction formed a single monophyletic cluster of P. blumei with bootstrap values ranging from 99% to 100%. A genetic distance of 0.00% among populations from Central Sulawesi (PBPSST.1, PBPSST.2, PBPSST.3), North Sulawesi (JQ982056.1), and South Sulawesi (JQ982058.1) confirms that all P. blumei samples have very close genetic relationships.